Development and validation of the perceived compassion scale: a reliable tool for assessing patient-centered nursing care - Yasemin Erden; Ayşe Metin; Nurgul Karakurt; Ulviye Aydan Nacak (BMC Nursing)
Abstract Aim To develop and validate the perceived compassion scale in nursing care to measure compassion from the patient’s perspective. Background Compassion in nursing care is a Professional value that affects nurses’ decision-making and actions. It contributes to excellence in nursing practice and facilitates nursing care. Methods This study, designed as a methodological type, was conducted with 398 patients between October and March 2023. The study utilized the Personal Information Form, and a draft version of the Perceived compassion in nursing care as data collection instruments. The collected data were analyzed to assess validity and reliability. Validity analyses included content validity, Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA). Reliability was evaluated through Cronbach’s Alpha and the split-half method. Statistical analyses were conducted using SPSS 22 and AMOS. EFA was performed with the Kaiser-Meyer-Olkin (KMO) test and Bartlett’s test (KMO = 1284.5, P = 0.000), applying varimax rotation, while CFA verified the factor structure. Pearson correlation analysis was used to determine criterion validity. Results The content validity index for the scale reviewed by the expert panel was 0.80. In the component analysis, all item factor loadings exceeded 0.30, and the explained variance was 51.71%. The x²/SD ratio ranged from 2.37. Fit indices such as GFI, AGFI, CFI, NFI, TLI, IFI, PGFI, and PNFI ranged between 0.68 and 0.94. The RMSEA and SRMR values were both 0.068 in the confirmatory factor analysis. The Cronbach’s α coefficient for the scale, which includes two sub-dimensions and 19 items, was 0.922, with sub-dimension Cronbach’s α values ranging from 0.921 to 0.931. Conclusions The Scale of Perceived Compassion in Nursing Care is a valid and reliable tool for assessing the impact of perceived compassion in nursing care from the patient’s perspective. Implications for nursing policy The Perceived Compassion Scale provides a foundation for policies emphasizing patient-centered care and integrating compassion metrics into healthcare quality assessments. Clinical trial number Not applicable.